ABA and the ubiquitin E3 ligase KEEP ON GOING affect proteolysis of the Arabidopsis thaliana transcription factors ABF1 and ABF3. (19th July 2013) - Chen, Yi‐Tze; Liu, Hongxia; Stone, Sophia; Callis, Judy
Summary The ABA Binding Factor/ABA‐Responsive Element Binding Proteins (ABF/AREB) subfamily of bZIP‐type transcription factors are positive effectors of ABA responses. Here, we examine the proteolytic regulation of two members: Arabidopsis thaliana ABF1 and ABF3. Both transcription factors are unstable in seedlings, and their degradation is sensitive to proteasome inhibition. ABA treatment of seedlings leads to their rapid accumulation, the result of slowed proteolysis. Deletion of the conserved C–terminal region required for 14–3–3 interaction destabilizes the proteins. The degradation of ABF1 and ABF3 are slower in vivo in seedlings lacking the ubiquitin E3 ligase KEEP ON GOING (KEG), and in vitro in extracts from keg seedlings, implicating KEG in their degradation. ABF1 and ABF3 are ubiquitylation substrates of KEG in vitro, and in vitro pull‐down assays document their direct interaction. In contrast to ABI5, another KEG substrate, the degradation of ABFs and proteolytic regulation of ABFs by ABA still occurs in keg seedlings, suggesting that additional E3s participate in ABF1 and ABF3 proteolysis. Loss of ABF1 or ABF3 in the keg background has a phenotypic effect similar to the loss of ABI5, and there is no additional rescue of the keg phenotype in abf1 abf3 abi5 keg seedlings. This result suggests that the abundance of other substrates is altered in keg seedlings, affecting growth. In conclusion, ABF1 and ABF3 abundance is affected by ABA and KEG, and the conserved C4 region serves as a stabilizing element.